Determinants of birth preparedness and complication readiness practice among reproductive-age women in Africa a systematic review and meta-analysis - Abebaw Alamrew; Assefa Sisay; Mulat Ayele; Eyob Shitie Lake; Getinet Kumie; Haimanot Hailu Mossie; Tadele Emagneneh; Chalie Mulugeta (BMC, 2024)
Abstract Background Safe motherhood programs must include both readiness for complications and childbirth. Birth preparedness and complication readiness (BPCR) is a comprehensive approach that helps resolve delays in deciding to seek care for obstetric problems. Objectives To identify the determinants of BPCR practice among reproductive age group women in Africa. Design Systematic Review and Meta-Analysis. Data sources and methods Preferred Reporting Items for Systematic Reviews and meta-analysis (PRISMA) were followed and databases such as MEDLINE, PubMed, Scopus, Hinari, Google Scholar, and Web of Science were used to find the available studies. Adjusted Odds Ratio (AOR) with 95% Confidence Interval (CI) was used to identify associated factors. I2 statistics, funnel plot, and Egger test were used to assess the studies' heterogeneity and publication bias. Results In this review, a total of 32 studies with 17,787 sample sizes were included. Knowledge of BPCR (AOR = 2.12, 95% CI: 1.44, 3.13), knowledge of danger signs during pregnancy (AOR = 1.60; 95% CI: 1.37, 1.88), Knowledge of labor and delivery danger signs (AOR = 1.44; 95% CI: 1.28, 1.62), Knowledge of postpartum danger signs (AOR = 1.40; 95% CI: 1.21, 1.63), urban residency (AOR = 1.32; 95% CI: 1.03, 1.70), Antenatal Care follow-up (AOR = AOR = 1.52;95% CI:1.42, 1.63), history of stillbirth (AOR = 1.59; 95% CI: 1.36, 1.86), parity (AOR = 1.76; 95% CI: 1.16, 2.66) and secondary or higher educational status (AOR = 1.51: 95% CI: 1.35, 1.68) were the determinants of BPCR practice. Conclusion BPCR practice among African women of reproductive age has been greatly affected by antenatal care visits, urban residency, knowledge of danger during pregnancy, labor, and postpartum, history of stillbirth, primiparity, and secondary or higher education. Focused interventions that address the identified factors may enhance BPCR practices and maternal health outcomes in Africa.